Omicron B.1.1.529 variant infections associated with severe disease are uncommon in a COVID-19 under-vaccinated, high SARS-CoV-2 seroprevalence population in Malawi. (February 2023) - Mseka, Upendo L.; Mandolo, Jonathan; Nyoni, Kenneth; Divala, Oscar; Kambalame, Dzinkambani; Mapemba, Daniel; Kamzati, Moses; Chibwe, Innocent; Henrion, Marc Y.R.; Manda, Kingsley; Thindwa, Deus; Mvula, Memory; et al.
Summary: Background: The B.1.1.529 (Omicron) variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in the fourth COVID-19 pandemic wave across the southern African region, including Malawi. The seroprevalence of SARS-CoV-2 antibodies and their association with epidemiological trends of hospitalisations and deaths are needed to aid locally relevant public health policy decisions. Methods: We conducted a population-based serosurvey from December 27, 2021 to January 17, 2022, in 7 districts across Malawi to determine the seroprevalence of SARS-CoV-2 antibodies. Serum samples were tested for antibodies against SARS-CoV-2 receptor binding domain using WANTAI SARS-CoV-2 Receptor Binding Domain total antibody commercial enzyme-linked immunosorbent assay (ELISA). We also evaluated COVID-19 epidemiologic trends in Malawi, including cases, hospitalisations and deaths from April 1, 2021 through April 30, 2022, collected using the routine national COVID-19 reporting system. A multivariable logistic regression model was developed to investigate the factors associated with SARS-CoV-2 seropositivity. Findings: Serum samples were analysed from 4619 participants (57% female; 60% aged 18–50 years), of whom 878/3794 (23%) of vaccine eligible adults had received a single dose of any COVID-19 vaccine. The overall assay-adjusted seroprevalence was 83.7% (95% confidence interval (CI), 79.3%–93.4%). Seroprevalence was lowest among children <13 years of age (66%) and highest among adults 18–50 years of age (82%). Seroprevalence was higher among vaccinated compared to unvaccinated participants (1 dose, 94% vs. 77%, adjusted odds ratio 4.89 [95% CI, 3.43–7.22]; 2 doses, 97% vs. 77%, aOR 6.62 [95% CI, 4.14–11.3]). Urban residents were more likely to be seropositive than those from rural settings (91% vs. 78%, aOR 2.76 [95% CI, 2.16–3.55]). There was at least a two-fold reduction in the proportion of hospitalisations and deaths among the reported cases in the fourth wave compared to the third wave (hospitalisations, 10.7% (95% CI, 10.2–11.3) vs. 4.86% (95% CI, 4.52–5.23), p < 0.0001; deaths, 3.48% (95% CI, 3.18–3.81) vs. 1.15% (95% CI, 1.00–1.34), p < 0.0001). Interpretation: We report reduction in proportion of hospitalisations and deaths from SARS-CoV-2 infections during the Omicron variant dominated wave in Malawi, in the context of high SARS-CoV-2 seroprevalence and low COVID-19 vaccination coverage. These findings suggest that COVID-19 vaccination policy in high seroprevalence settings may need to be amended from mass campaigns to targeted vaccination of reported at-risk populations. Funding: Supported by the Bill and Melinda Gates Foundation (INV-039481 ).